Sintesis dan Karakterisasi Silika Gel dari Limbah Botol Kaca sebagai Adsorpsi Ion LOgam Berat (Pb) pada Air Pasca Tambang (Kolong) di Bangka - Livia Livia; Widodo Budi Kurniawan; Dewi Marina; Sitti Patimah Wati (Jurusan Fisika, Universitas Bangka Belitung, 2020)
Glass bottle waste is inorganic waste that cannot be broken down by microorganisms. The high SiO2 content in glass bottle waste has the potential as a base material in the synthesis of silica gel. This study aims to determine the characteristics and ability of silica gel as adsorption of Pb metal ions in water under Bangka. The stages in this study were started from the extraction of silica from waste glass bottles, synthesis of silica gel, activation with HCl and testing the adsorption of Pb metal ions in under water. The results showed that the characteristics of silica gel with variations of 100 and 200 mesh, the concentration of 3M NaOH, 3M HCl using SEM EDS had an amorphous structure and the SiO2 content graph had high peaks. In the BET test, the pore radius was 1164.207 for the 100 mesh sample and 1293.102 for the 200 mesh sample. The AAS results showed that in the treatment of 100 mesh, the Pb value decreased by -0.1122, while for 200 mesh also decreased by -0.1322. The Pb value is minus because the tool can only read with a standard limit of 0.1. If it is less than 0.1, then the tool cannot read the value on Pb metal even though the value is minus but has a value. The greater the minus, the lower the Pb value. So silica from glass bottle waste can adsorb heavy metals (Pb) on the surface water underneath